Sacubitril Ameliorates Cardiac Fibrosis Through Inhibiting TRPM7 Channel - Jia, Tian; Wang, Xiaozhi; Tang, Yiqun; Yu, Wenying; Li, Chenhui; Cui, Shufang; Zhu, Juanjuan; Meng, Wei; Wang, Chen; Wang, Quanyi (Frontiers in Cell and Developmental Biology, 2021)
Heart failure caused by cardiac fibrosis has become a major challenge of public health worldwide. Cardiomyocyte programmed cell death (PCD) and activation of fibroblasts are crucial pathological features, both of which are associated with aberrant Ca2+ influx. Transient receptor potential cation channel subfamily M member 7 (TRPM7), the major Ca2+ permeable channel, plays a regulatory role in cardiac fibrosis. In this study, we sought to explore the mechanistic details for sacubitril, a component of sacubitril/valsartan, in treating cardiac fibrosis. We demonstrated that sacubitril/valsartan could effectively ameliorate cardiac dysfunction and reduce cardiac fibrosis induced by isoprotereno (ISO) in vivo. We further investigated the anti-fibrotic effect of sacubitril in fibroblasts. LBQ657, the metabolite of sacubitril, could significantly attenuate transforming growth factor-β 1 (TGF-β1) induced cardiac fibrosis by blocking TRPM7 channel, rather than suppressing its protein expression. In addition, LBQ657 reduced hypoxia-induced cardiomyocyte PCD via suppression of Ca2+ influx regulated by TRPM7. These findings suggested that sacubitril ameliorated cardiac fibrosis by acting on both fibroblasts and cardiomyocytes through inhibiting TRPM7 channel.